Home accidents in the province of Trento. Ten years of observations regarding admissions to the emergency and first aid department - Piffer, S.; Demonti, S.; Ramponi, C.; Giustini, M.; Pitidis, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Home accidents, or domestic accidents, are accidents that occur inside a home or the adjacent areas (stairways, courtyards, gardens, attics, cellars, garages, etc.). In Italy, they are monitored through a number of surveillance systems including the PASSI system and the ISTAT (Italian Institute of Statistics) Multipurpose Survey on Households. Only the SINIACA system (Italian National Information Service on Domestic Accidents), managed by the Istituto Superiore di Sanità (National Institute for Health), provides health-related information regarding such events and their circumstances and consequences, based primarily on Accident & Emergency Departments’ data. Study design. This is an observational study on the domestic accidents trends in the province of Trento, using data on Accident & Emergency Departments admissions, between 2009 and 2018, combined with mortality and hospital discharge data. Methods. The authors extrapolated records regarding admissions for domestic accidents from the digital annual Accident & Emergency admissions archive. For the 2009-2018 period, they analysed: the trend over time, both overall and classified according to gender and age group; and the inflow rate/10,000 inhabitants, broken down according to gender, nationality (Italians and foreign nationals) and age group. The coverage of the additional SINIACA variables regarding the accident dynamic, contingent activity and place of the accident were also analysed. With regard to the case load for 2018, the authors analysed the site and type of the injuries, the level of severity, outcome and the services provided, comparing the 0-14 years and >65 years age groups. Trend significance was analysed using the Cochran-Armitage test for trend and the significance of the differences between the proportions was analysed using the Chi-squared test. We have also calculated the costs of the services provided, overall and by age group. Results. During the study period, a total of 99,386 A&E admissions for domestic accidents were recorded, with an annual average of 9,938 admissions. Between 2009 and 2018, there was a statistically significant increase of 41%, which was due in part to better event recognition and recording. Females prevail over males, especially over the age of 75 years. Over time there is an increase in cases over the age of 65, due to the progressive ageing of the population. Considering the resident population alone, the A&E inflow rate rises from 147 admissions/10,000 inhabitants in 2009 to 197 admissions/10,000 inhabitants in 2018, with a 39.0% increase. Inflow is greater in the two extreme age groups: in 2018, in the 0-4 years age group, the inflow rate is 319 admissions/10,000 inhabitants and in the over 75 years class it rises to 481 admission/10,000 inhabitants, 1.6 and 2.4 times the mean inflow for home accidents in the province of Trento, respectively. Admissions are less amongst foreign nationals than amongst Italians. Generally speaking, the events were of a mild severity, with white triage codes accounting for 16% of cases and green triage codes for 73%. The degree of severity is higher amongst subjects aged over 65, as well as in women and Italian citizens.The level of recording of SINIACA variables increases over time, to reach 100% coverage in 2018. Falls are the most common dynamic in all age ranges; household chores, activities of daily living and DIY are the three most commonly observed activities. Home accidents most commonly occur in the areas adjacent to the home and the kitchen. In over 2/3 of cases, the injuries sustained were to the limbs and the head/face. Head/face injuries prevail in the youngest age group. Wounds, burns and head injuries are the most common types of injury sustained by children in the 0-14 years age group, whereas fractures and dislocations are typical of the older age groups. Diagnostic and care resource consumption is far higher amongst the elderly, which absorb 61% of the total costs of the cases treated in the year 2018. Conclusions. Accident & Emergency facilities provide a privileged observatory for the monitoring of domestic accidents in the population. By comparing our data with the ISTAT data, it can be estimated that 1 in 2 home accidents in the population resulted in an A&E admission. Admissions increase over time, particularly amongst the elderly and they are not higher amongst foreign nationals than amongst Italians. The inflow rate is higher in the extreme age ranges: 0-4 and >75 years; however, there are differences between the two in terms of type of injury, level of severity and outcome. It is essential for A&E admission data to be fully digitalised, and facility and staff sensitisation is also important in order to guarantee the availability of good-quality data. The completeness of A&E data and the possibility of obtaining case stratification based on social and demographic characteristics could make it possible, through a virtuous integration of services, to use these data for the implementation of prevention initiatives. These, if carried out effectively, could also contribute to contain healthcare costs.